Comparative Study of Multi-slice CT between Normal Duodenal Papilla and Duodenal Papillary Carcinoma - Junjie REN; Chenjie AN; Xiaoguang LI; Huiying ZHANG (CT Lilun yu yingyong yanjiu, 2022)
Objective: In order to provide more imaging information for duodenal papillary carcinoma, we explored the CT manifestations of the normal duodenal papilla and duodenal papillary carcinoma. Methods: We performed retrospective analysis on the CT data of 40 cases with normal duodenal papilla and 12 cases with duodenal papillary carcinoma confirmed by pathology, all the cases underwent hypotonic multi-slice spiral CT for the contrastive analysis of the CT manifestations. Results：Most of the normal duodenal papillas had round shapes, and were mainly located in the posterior-lateral inner wall of the middle-lower descending part of duodenum (100%, 40/40), whose maximum diameter was (8.31±1.29) mm. Enhanced scan resulted in obvious enhancement in arterial phase, continued enhancement in portal venous phase and decreased enhancement in equilibrium phase, whose density was still higher that that of plain scan. In the cases with duodenal papillary carcinoma, we saw lobular, round or oval soft tissue masses in the duodenal papilla region, whose maximum diameter was (21.47±2.49) mm. MPR and CPR showed that gourd-shaped (Inverted "3") soft tissue masses protruded into the duodenal lumen. Enhanced scan resulted in homogeneous mild-moderate enhancement in arterial phase, increased enhancement in venous phase and decreased enhancement in equilibrium phase. The intrahepatic and extrahepatic bile ducts expanded, gallbladders magnified while the common bile duct and pancreatic duct expanded and got cut off at the papillary tumor, which showed “double duct sign”. Conclusion: The structure of ampulla under the filling state of hypotonic duodenum can be clearly displayed. The combination of multiplanar reconstruction (MPR) and curved surface reconstruction (CPR) is helpful to the diagnosis of duodenal papillary carcinoma